Examining the Relationship Between Leisure Time Physical Activity Constraints and Healthy Lifestyle Behaviors Among University Students - Bengisu Tüfekçi; Aliye Bulut (Galenos Yayinevi, 2024)
Objective: The aim of this study is to examine the relationship between leisure time and physical activity constraints and healthy lifestyle behaviors among university students and to determine possible differences according to sociodemographic and physical characteristics. Materials and Methods: The participants were reached using the purposeful sampling method, which is an improbable sampling method, and students from a public university located in a province in Southeastern Anatolia were accepted as the target group. The study population consisted of students who received health education at the level of associate degree (n=380). The questionnaire created by the researchers comprises three parts. The first part of the form consisted of descriptive questions that query the sociodemographic characteristics, the second part consisted of the Scale of Leisure Time Physical Activity Constraints, and the third part consisted of the Healthy Life Style Behavior Scale-II form. Results: In the present study, sociodemographic characteristics of the participants, such as gender, persons sharing living quarters, transportation preferences, and regular exercise, were effective in reducing leisure physical activity constraints, and the department they studied at the university, gender, and regular exercise were effective in reducing healthy lifestyle behaviors, as well. In addition, as a result of the present study, it was determined that leisure time and physical activity constraints have a negative effect on healthy lifestyle behaviors. Conclusion: Interventions to reduce physical activity constraints may also have a positive effect on a healthy lifestyle.